Impact of telework an journalistic routines - Muñoz Montenegro, Marisa (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
Covid-19 brought with it numerous repercussions for people´ s lives, considering the way we communicate one of the most visible, establishing teleworking as the safest way to sustain an economy in crisis. From a theoretical point of view, the present reaserch is based on the concepts of newsmaking and agenda setting theory, in addition to the notion of gender linked to stereotype to analyze how the broadcast elaboration process changed during the pandemic in its initial stage. This affected the procedure of constructing news and accentuated gender gaps amoung journalists that are perpetuated until today. The present reaserch analyzes, through semi- estructured interviews, through 14 Chilean reporters, the impact of teleworking on the jornalistic routine.